The Influence of Share Ownership on Dividend Policy in Consumer Goods Companies in Indonesia - Nurwanda Wardhayat, Darrel; Usman, Bahtiar (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to examine the influence of foreign ownership, director ownership, institutional ownership on dividend policy. The control variables in this research consist of profitability and business risk. Data collection used purposive sampling method sourced from annual reports of consumer goods companies listed on Indonesia Stock Exchange (BEI). The number of samples in the study was 35 companies for the period 2018 to 2022. In testing the hypothesis using the panel data regression method. The results of this study indicate that foreign ownership does not have a significant influence on dividend policy. Director ownership has a significant positive effect, while institutional ownership has a significant negative effect on dividend policy. The results of the control variables show that profitability has a positive effect on dividend policy. Meanwhile, business risk has a negative influence on dividend policy. The implications of this research for financial managers are expected to have a deep understanding in formulating assessments and assist managers related to dividend policy. Meanwhile, investors can thoroughly analyze risks and results of business growth related to investments made in relation to factors such as Foreign Share Ownership, Board of Directors Share Ownership, Institutional Ownership, Profitability and the company's Business Risk.